Sitgreaves family papers
ALS (1801 March 19) written by Rufus King to Samuel Sitgreaves relating to national politics; ALS (1808 September 1) written by Samuel Sitgreaves to John Arndt relating to the electoral college and the Federal Party; and ALS (1875 December 21) written by Henry C. Wayne to Lorenzo Sitgreaves concerning Gen. Thomas Sidney Jesup.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Arndt, John, -- active 1808 -- Correspondence; Jesup, Thomas Sidney, -- 1788-1860.; King, Rufus, -- 1755-1827 -- Correspondence; Sitgreaves, Lorenzo, -- 1811-1888 -- Correspondence; Sitgreaves, Samuel, -- 1764-1827 -- Correspondence; Wayne, Henry C. -- 1815-1883 -- Correspondence; Sitgreaves family; Federal Party (U.S.); Electoral college; United States -- Politics and government -- 1801-1809.